(untitled) (Research, Society and Development, 2021)
This study aims to analyze and evaluate the quality of life in the recovery of patients in the postoperative period in vascular surgeries. Methods: this is an integrative literature review, which carried out a bibliographic search in the following databases, selected through the CAPES Periodic Portal metabolisador: Scientific Electronic Library Online (SciELO), Medical Literature Analysis and Retrievel System Online ( Medline) and Latin American and Caribbean Literature in Health Sciences (LILACS), using the descriptors “Vascular surgery”, “Postoperative” and “Quality of life”, which were searched in the Health Sciences Descriptors (DECs) . After analytical reading, only 14 articles met the inclusion criteria and were used to compose the final sample of this study. Articles that were classified as studies with human beings and published between 2010 and 2020 were used. Results: the surgical technique has a great influence on the evolution of the patient’s clinical condition. New techniques appear with the objective of being less invasive and providing a better recovery. However, some pathologies, being serious, still have a high rate of mortality and complications. Conclusion: Patients with vascular diseases need special care in order to avoid complications in the postoperative period and ensure a good quality of life. It was observed that in addition to the severity of the disease, the assessment of the reality that the patient is inserted has considerable importance in the quality of life, since the biopsychosocial factors have a significant impact on the illness process.